EFFECTS OF ISOTRETINOIN ON PSYCHOLOGICAL WELL-BEING AND MENTAL HEALTH: A NARRATIVE REVIEW - Ewa Dapkiewicz; Sylwia Haba; Dawid Gąsowski; Jan Szewczyk; Alicja Smolińska; Maria Bołoz; Zuzanna Wątek; Katarzyna Łysynkiewicz; Patrycja Krawczyk (Archiv Euromedica, 2026)
Background Isotretinoin is an effective treatment for severe and treatment-resistant acne vulgaris, but concerns persist regarding possible psychiatric adverse effects, including depression, anxiety, suicidal behaviour, and other psychiatric manifestations. Interpretation of these outcomes is complicated by the substantial psychological burden of acne itself and by changes in quality of life during successful treatment. Aim To evaluate current evidence regarding the association between isotretinoin therapy and mental health outcomes, with particular attention to potential neurobiological mechanisms, clinical and epidemiological findings, and the psychological burden of acne. Materials and Methods A narrative review was conducted using PubMed/MEDLINE and Google Scholar. English-language publications from 1982 to 2026 were considered, with priority given to more recent clinical and epidemiological evidence. Eligible sources included clinical and observational studies, cohort studies, case reports and case series, experimental and preclinical studies, systematic reviews, meta-analyses, clinical guidelines, consensus statements, and narrative reviews. Of 87 potentially relevant publications identified, 61 were included in the final narrative synthesis. Results Experimental and neurobiological studies suggest biologically plausible mechanisms related to retinoid signalling, serotonergic neurotransmission, hippocampal neurogenesis, and brain regions that regulate emotional processes. However, large observational studies and meta-analyses have generally not demonstrated an increased population-level risk of depression, anxiety, suicidal behaviour, or other psychiatric disorders among isotretinoin users. Rare individual psychiatric reactions have been reported, particularly in patients with pre-existing psychiatric vulnerability. Acne itself is associated with depression, anxiety, reduced self-esteem, impaired quality of life, and suicidal ideation, while successful treatment may be accompanied by improvements in psychological well-being. Conclusions Current evidence does not support a definitive causal relationship between isotretinoin therapy and psychiatric disorders. Mental health outcomes should be interpreted in the context of baseline psychiatric status, acne severity, treatment response, and changes in quality of life. Baseline mental health assessment and regular monitoring during isotretinoin therapy remain advisable.